The Challenge to Indonesian Social Studies Education in Teaching Democratic Values - Fattah Hanurawan; Peter Waterworth (Universitas Negeri Malang, 2016)
Processes of democratization in Indonesia occur at a rapid pace in many areas of public discourse. It is therefore necessary for the education system to keep abreast of the changes in community. Demand for the political renewal of the society exemplifies democratic processes in its structures and processes as well as preparing students to understand democracy. This article argues that schools and other educational institutions need to demonstrate open and critical democratic processes in the way that they operate as a prerequisite for teaching students how to adopt the roles of responsible citizens within a truly democratic environment. It explores strategies that teachers may adopt to democratize their curriculum and pedagogy